2010
DOI: 10.1016/j.devcel.2009.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Structural Rules and Complex Regulatory Circuitry Constrain Expression of a Notch- and EGFR-Regulated Eye Enhancer

Abstract: SUMMARY Enhancers integrate spatiotemporal information to generate precise patterns of gene expression. How complex is the regulatory logic of a typical developmental enhancer, and how important is its internal organization? Here, we examine in detail the structure and function of sparkling, a Notch- and EGFR/MAPK-regulated, cone cell-specific enhancer of the Drosophila Pax2 gene, in vivo. In addition to twelve previously identified protein binding sites, sparkling is densely populated with previously unmapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
183
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(193 citation statements)
references
References 47 publications
10
183
0
Order By: Relevance
“…Over many years, these analyses have shed light on the logic of cis-regulation (Istrail and Davidson, 2005). Furthermore, they have provided invaluable insights into the structural rules (Erives and Levine, 2004;Panne et al, 2007;Swanson et al, 2010) and evolutionary histories (Ludwig and Kreitman, 1995;Crocker et al, 2008) of enhancers. Nevertheless, it is widely recognized in the cis-regulation community that, often, small enhancer elements do not faithfully recapitulate native expression patterns (Barolo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over many years, these analyses have shed light on the logic of cis-regulation (Istrail and Davidson, 2005). Furthermore, they have provided invaluable insights into the structural rules (Erives and Levine, 2004;Panne et al, 2007;Swanson et al, 2010) and evolutionary histories (Ludwig and Kreitman, 1995;Crocker et al, 2008) of enhancers. Nevertheless, it is widely recognized in the cis-regulation community that, often, small enhancer elements do not faithfully recapitulate native expression patterns (Barolo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…each transcription factor can recognize a variety of binding site sequences. In addition, although some examples of rigid enhancer organization exist [2,3], the order of TFBSs on a given enhancer can be quite flexible [4]. Finally, enhancers act at a distance and can even be embedded within neighbouring loci [5][6][7][8][9], indicating a large degree of positional freedom of enhancers in relation to the genes they control.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have shown that enhancers contain clusters of transcription factor (TF) binding sites within blocks of conserved sequences (Berman et al, 2004; Brody et al, 2012; Davidson & Erwin, 2006; Swanson, Evans, & Barolo, 2010), it is not yet well understood just how the distribution of these sites provides a basis for combinatorial logic of enhancer function. One entry point into deciphering the rules that govern an enhancer's ability to direct gene expression is to manipulate the internal organization of enhancers, that is, position, frequency, and/or order of functionally relevant sequences and examine the effects on cis ‐regulatory behavior.…”
Section: Introductionmentioning
confidence: 99%
“…One entry point into deciphering the rules that govern an enhancer's ability to direct gene expression is to manipulate the internal organization of enhancers, that is, position, frequency, and/or order of functionally relevant sequences and examine the effects on cis ‐regulatory behavior. For example, altering the TF binding sites and other sequences within the sparkling enhancer of shaven (dPax), a gene that encodes a key regulator of photoreceptor fate specification in the developing Drosophila retina, switched the specificity of the enhancer from cone to rod photoreceptors (Swanson et al, 2010). A second study has shown that an enhancer of the Drosophila Suppressor of Hairless gene is composed of overlapping elements termed submodules that can function independently to activate enhancer activity (Liu & Posakony, 2014).…”
Section: Introductionmentioning
confidence: 99%